CT and MRI appearance of solitary parapelvic neurofibroma of the kidney - Eljack, S (The British Institute of Radiology., 2010)
We report an extremely rare case of a renal parapelvic neurofibroma. The mass was an incidental finding on an abdominal CT scan of an asymptomatic 59-year-old male with hepatitis C. Subsequent MRI demonstrated a complex mass occupying the left renal sinus that had mass effect on the pelvicalyceal system. The patient underwent left radical nephrectomy, and histological and immunohistochemical findings confirmed the lesion to be a neurofibroma. Given that similar imaging features have been reported previously in four additional cases, we suggest that it may be possible to include this entity in the pre-operative differential diagnosis.